'Open-sourcing' personal learning - Sebastian H. D. Fiedler (Journal of Interactive Media in Education, 2014)
This article offers a critical reflection on the contemporary Open Educational Resource (OER) movement, its unquestioned investment in a collective 'content fetish' and an educational 'problem description' that focuses on issues of scarcity, access, and availability of quality materials. It also argues that OER proponents fail to take notice of historically new forms of learning activity emerging within the unfolding digital transformation of our global society. The article reviews some descriptive accounts of such learning activity and suggests that 'networked autodidaxy' in particular can provide inspiration for the critical review of our ideas regarding open resources and practices in education